2014
DOI: 10.22456/2316-2171.25854
|View full text |Cite
|
Sign up to set email alerts
|

Consumo De Medicamentos Por Idosos De Uma Unidade Básica De Saúde De Rondonópolis/Mt

Abstract: O presente trabalho teve por objetivo avaliar o consumo de medicamentos por idosos usuários da Unidade Básica de Saúde Dom Bosco do município de Rondonópolis/MT. Trata-se de uma pesquisa prospectiva e transversal. Participaram do estudo 238 indivíduos de ambos os sexos, com 60 anos ou mais, cadastrados na UBS. O instrumento utilizado foi uma entrevista com questões abertas e fechadas referentes a características sociais, condições de saúde, uso de serviços de saúde e consumo de medicamentos. Os dados foram col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
0
0
5
Order By: Relevance
“…The overall prevalence of medication use observed in this study (81.8%) was higher than that of other studies carried out in PHCs in Brazil 11,[16][17][18] and those with a national 1,[6][7][8]19,20 and international 21,23 population base. Specifically, the prevalence of medication use in the age group of 65 years or older (90%) was similar to that of national studies in PHCs 16 REV BRAS EPIDEMIOL 2020; 23: E200025 and population-based studies 20,24 , but higher than that found in studies conducted exclusively with the elderly both in PHCs 25,26 and in population-based setting 19,27,28 . The mean number of drugs consumed per individual (2.67) was similar to that of studies carried out in PHCs in Brazil 16 and in other countries 29 , but higher than that of other studies 7,8,17,22,30 , whose averages ranged between 1.5 and 2.2.…”
Section: Discussionsupporting
confidence: 70%
“…The overall prevalence of medication use observed in this study (81.8%) was higher than that of other studies carried out in PHCs in Brazil 11,[16][17][18] and those with a national 1,[6][7][8]19,20 and international 21,23 population base. Specifically, the prevalence of medication use in the age group of 65 years or older (90%) was similar to that of national studies in PHCs 16 REV BRAS EPIDEMIOL 2020; 23: E200025 and population-based studies 20,24 , but higher than that found in studies conducted exclusively with the elderly both in PHCs 25,26 and in population-based setting 19,27,28 . The mean number of drugs consumed per individual (2.67) was similar to that of studies carried out in PHCs in Brazil 16 and in other countries 29 , but higher than that of other studies 7,8,17,22,30 , whose averages ranged between 1.5 and 2.2.…”
Section: Discussionsupporting
confidence: 70%
“…A maior porcentagem de idosos usuários do SUS que declaram não realizar exercício físico também esteve presente em estudo nacional, com percentual de 71,85% (GOULART et al, 2014). Este resultado pode ser avaliado a partir de duas perspectivas: por um lado, sabe-se que as USFs oferecem grupos de atividade física, aulas de dança e ginástica coordenados pelo Núcleo de Apoio à Saúde da Família (NASF), em sua maioria voltados para este público-alvo, com o objetivo principal de prevenir incapacidades funcionais, porém a demanda ainda se mantém muito aquém das necessidades apresentadas por estas pessoas.…”
Section: Discussionunclassified
“…No Brasil em 2017, o número de idosos com 60 anos ou mais ultrapassou um percentual de 30,2 milhões e, com isso, entende-se que esse fenômeno está relacionado com a mudança de hábitos da sociedade e com a transição demográfica observada nos últimos anos (Flores et al, 2019). Do ponto de vista epidemiológico, os idosos representam a faixa etária que mais frequentam os serviços de saúde devido ao desenvolvimento de doenças crônicas associado às mudanças fisiológicas do avançar da idade que culminam em um declínio progressivo e funcional, bem como cognitivo, psíquico e social (Goulart et al, 2014). Tais alterações fisiológicas estão geralmente associadas a polifarmácia, tornando-os mais expostos à utilização de medicamentos potencialmente inapropriados, a maior propensão a ocorrência de interações medicamentosas, bem como reações adversas aos medicamentos (RAM) (Rodrigues & Oliveira, 2016).…”
Section: Introductionunclassified